New onset of generalized myasthenia gravis developed after a new coronavirus infection (COVID-19) - T. M. Alekseeva; P. Sh. Isabekova; M. P. Topuzova; N. V. Skripchenko (Журнал инфектологии, 2021)
Development of various immune-mediated neurological complications after a viral infection is of particular interest to medical society during a pandemic of COVID-19. It was found that SARS-CoV-2 has the ability to cause hyperstimulation of the immune system, thereby initiating developing of autoimmune diseases. The article describes a clinical case of new onset of generalized myasthenia gravis with thymoma in a patient after previous COVID-19.